ANALISIS KETIDAKTEPATAN SASARAN BANTUAN SOSIAL DI KOTA MEDAN: STUDI LITERATUR TERHADAP IMPLEMENTASI KEBIJAKAN - Legi Likasri Simbolon; Nazwa Aulia; Olive Katrina Joyanka Sihombing; Samuel Revaldo Jeverson Siboro; Ruben Boot (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
Social Assistance (Bansos) is a government program aimed at providing economic protection for poor and vulnerable households. However, its implementation in Medan City still faces issues related to mistargeting of beneficiaries. This study analyzes the factors contributing to the mistargeting of social assistance distribution using a descriptive qualitative method through a literature review of scientific journals, government reports, and credible news sources. The results indicate that mistargeting occurs mainly due to inaccuracies in the Integrated Social Welfare Data (DTKS), weak factual verification at the village level, limited public transparency, and political or social interests affecting beneficiary determination. These conditions lead to exclusion and inclusion errors, trigger social jealousy, and reduce public trust in local government. Improving data management, enhancing staff capacity, strengthening transparency, and increasing community monitoring are essential efforts to ensure that social assistance is more accurately targeted in the future.